2014
DOI: 10.7150/thno.8715
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Associated With HBV Infection And HBV-related HCC

Abstract: Hepatitis B virus (HBV) infection is a global problem and a major risk factor for hepatocellular carcinoma (HCC). microRNAs (miRNAs) comprise a group of small noncoding RNAs regulating gene expression at the posttranslational level, thereby participating in fundamental biological processes, including cell proliferation, differentiation, and apoptosis. In this review, we summarize the roles of miRNAs in HBV infection, the recently identified mechanism underlying dysregulation of miRNAs in HBV-associated HCC, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 153 publications
(154 reference statements)
3
79
0
1
Order By: Relevance
“…Therefore, the consequence of the inhibition of PTEN by miR21 is the activation of the PI3K/AKT pathway, which promotes cancer cell proliferation and metastasis (28). miR221/222 acts on many key tumor suppressors, including Bmf (29) (35). Among the HBV-related miRNAs, miR1 and miR501-5p can promote HBV replication, thereby promoting the occurrence and progression of HCC (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the consequence of the inhibition of PTEN by miR21 is the activation of the PI3K/AKT pathway, which promotes cancer cell proliferation and metastasis (28). miR221/222 acts on many key tumor suppressors, including Bmf (29) (35). Among the HBV-related miRNAs, miR1 and miR501-5p can promote HBV replication, thereby promoting the occurrence and progression of HCC (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study examined the effect of a family history of HCC on the incidence of HCC in the entire population who were screened for HBV seromarkers, and elucidated that family history of HCC multiplied the risk of HCC at each stage of HBV infection (7). Although numerous molecular studies have revealed that the HBV-encoded X (HBx) protein performs a critical role in hepatocarcinogenesis in patients with HBV-associated HCC (9)(10)(11)(12), the mechanisms underlying familial clustering-associated carcinogenesis remain to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) comprise a group of small noncoding RNAs which regulate gene expression at the posttranslational level, thereby participating in fundamental biological processes including cell proliferation, differentiation, and apoptosis (Karakatsanis et al, 2013;Wang et al, 2014a;Xie et al, 2014). miRNAs have been proposed to represent ideal biomarker candidates because of their resistance to endogenous RNase resistance and high stability under different storage conditions (Schwarzenbach et al, 2014) and in the peripheral blood (Zhu et al, 2012;Wang et al, 2014c).…”
Section: Introductionmentioning
confidence: 99%